Selection of new common bean lines for high grain quality and mineral concentration - Dalfollo Ribeiro, Nerinéia; Godoy dos Santos, Greice; Rosana Kläsener, Greice; Fuzzer de Andrade, Fabrício; da Silva Argenta, Henrique (Revista Ciência Agronômica, 2022)
The development of new common bean lines with traits that meet consumer preference increases their probability of use as food. The objectives of this work were to evaluate the genetic variability of common bean lines and cultivars for grain quality traits and mineral concentration and to select superior lines using the rank-sum index with differentiated economic weights. The experiments were carried out in two growing seasons to evaluate 17 common bean genotypes. The ten grain quality traits and the concentration of seven minerals were determined in raw grains. A significant effect for genotype was observed for 15 traits and a significant genotype x environment interaction was found for 14 traits. High heritability (≥ 60.00%) and genetic gain estimates favorable to the objectives of selection of superior light-and dark-grain common bean lines for most of grain quality traits and mineral concentration were obtained. The common bean lines and cultivars show genetic variability for all grain quality traits and mineral concentration, except for copper concentration. Four carioca (LEC 04-16, Linhagem 110, UEM 266 and Pérola) and four black (TB 17-03, SM 1510, BRS Intrépido and Fepagro Triunfo) common bean genotypes are superior for several grain quality traits and have high concentrations of potassium, phosphorus, calcium and iron, showing potential for use in breeding and nutrition.